Silent Scenes in Manga as the Powerful and Universal Visual Languages - Hafiz Aziz Ahmad (Wimba : Jurnal Komunikasi Visual, 2012)
Comics as the popular medium of communication, especially medium for the children due to its capabilities in telling stories with its visual narrative has been known for quite long. Manga as the form of comic medium that came from Japan is also well known for its uniqueness. Due to the strong relation within the Japan cultural background, manga has integrated its own distinctive way in telling the stories, visually. One of the methods is known as the silent sequences. The silent sequences term is used to mention the scene in comics that told using minimal sequence and with very little -if any- text or narration. Some even used several of unconnected scenes to create a specific mood or a sense of place. Such scenes could be found in abundance in various manga works, notably in the works of Osamu Tezuka or Mitsuru Adachi. Scott McCloud "“a comic scholar- relates these sequences as the solid example of moment-to-moment and aspect-to-aspect type of panel transition. By using mostly visual images with less text and narration as the way of telling stories and creating the exact mood for the scenes, the silent sequences could serve as a good example of the universality and power of comic language. This paper is intended to take further analysis behind the context of the silent sequences and the possibilities in using it as a more universal way in visual communication as part of the power in children's literature.